Aquolab ® ozone-therapy is an efficient adjuvant in the treatment of chronic periodontitis: A case-control study - Francesco Carinci; Annalisa Palmieri; Ambra Girardi; Francesca Cura; Dorina Lauritano (Wolters Kluwer Medknow Publications, 2015)
Aim: The objective of this study was to compare the efficacy of supportive periodontal therapy (i.e., scaling and root planning [SRP]) alone versus Aquolab ® ozone therapy used in association with SRP in the treatment of chronic periodontitis in adult patients. Materials and Methods: A total of 20 patients with a diagnosis of chronic periodontitis (40 localized chronic periodontitis sites) were enrolled. None of these patients have previously received any surgical or nonsurgical periodontal therapy and demonstrated radiographic evidence of moderate bone loss. Two nonadjacent sites in separate quadrants were selected in each patient to verify treatment efficacy (split-mouth design). Microbial analysis was analyzed at baseline and the 7 th day after treatment. SPSS program and paired simple statistic t-test were used to detect statistically significant differences. Results: There was a statistically significant reduction of Tannerella forsythia loading in sites treated with ozone therapy respect to those treated with SPR alone. A similar trend was obtained also for additional 5 species and for total bacterial loading (CBT). These results were obtained with a single local application of ozone therapy just after SPR and with a molecular control 7 th day after treatment. Conclusion : Aquolab ® ozone therapy in is effective in reducing the CBT in pockets of patients affected by periodontitis. It is an efficacy medical device to be used as adjuvant therapy to be added to SRP in the management of moderate to severe chronic periodontitis.